Steers performance fed diets with Alexander grass silage (Urochloa plantaginea) x sorghum silage (Sorghum bicolor (L.) Moench) - Argenta, Flânia Mônego; Brondani, Ivan Luiz; Alves Filho, Dari Celestino; Restle, João; Segabinazzi, Luciane Rumpel; Cattelam, Jonatas; Silva, Viviane Santos da; Paula, Perla Cordeiro de; Azevedo Júnior, Ricardo Lima de; Klein, John Lenon; Adams, Sander Martinho; Teixeira, Odilene de Souza (Semina: Ciências Agrárias, 2014)
This study aimed to evaluate the parameters related to feedlot beef steers fed with Alexander grass silage or sorghum silage as roughage source. Twelve animals with initial average of weight and age of 245 kg and 20 months, respectively, belonging to Nellore (N), Charolais (C), 21/32 N 11/32 C, 21/32 C 11/32 N; 43/64 N 21/64 C and 43/64 C 21/64 N genetic groups were used. The ration was composed by a roughage:concentrate relation of 50:50 (dry matter basis), offered at ease. The dry matter, crude protein, ether extract, neutral detergent fiber and acid detergent fiber daily intake didn't differ between roughage sources, being the medium values of 10.18; 1.28; 0.20; 4.96 and 2.51 kg/day, respectively. However, the ether extract intake by metabolic size and by corporal weight percentage were higher for the one that consumed sorghum silage, obtaining values of 2.74 and 2.36 g/metabolic size and 0.06 and 0.05 kg/100 kg of live weight. The same behavior was observed for digestible energy intake, presenting values of 364.87 and 302.83 g/metabolic size and 8.10 and 7.02 kg/100 kg of live weight. The daily average gain, final corporal score and feed conversion weren't influenced by roughage type, being the values of 1.31 kg; 4.05 points and 7.78 kg of DM/kg of weight gain, respectively. The Alexander grass silage is a feasible alternative as its substitution in relation to sorghum silage.